2001
DOI: 10.1080/09638180126640
|View full text |Cite
|
Sign up to set email alerts
|

New opportunities for farm accounting

Abstract: There is a gap between the importance given to accounting and the low level of bookkeeping and accounting practice in the agricultural sector. Current general accounting rules do not adapt very well to the particularities of farming and are difficult and expensive to implement. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
13

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 14 publications
1
59
0
13
Order By: Relevance
“…As it can be seen in the figure above, the fair and book value differ from each other mainly in the early stages of the useful life of bearer plants. The difference decreases at the end of the useful life (this also confirms the conclusions of the study Argilés and Slof (2001), which dealt with comparing of the fair value and the carrying amount of biological assets in Spain and concluded that the differences in biological assets reporting through various methods of valuation are not significantly different). These arguments are in favour of the use of the cost model of the bearer plants measurement.…”
Section: Cost Model Applicationsupporting
confidence: 74%
“…As it can be seen in the figure above, the fair and book value differ from each other mainly in the early stages of the useful life of bearer plants. The difference decreases at the end of the useful life (this also confirms the conclusions of the study Argilés and Slof (2001), which dealt with comparing of the fair value and the carrying amount of biological assets in Spain and concluded that the differences in biological assets reporting through various methods of valuation are not significantly different). These arguments are in favour of the use of the cost model of the bearer plants measurement.…”
Section: Cost Model Applicationsupporting
confidence: 74%
“…Penggunaan model nilai wajar dalam IAS 41 untuk aset biologis dan hasil agrikultur ini diyakini merupakan standar akuntansi yang menyediakan a good conceptual framework (Argiles & Slof, 2001). Penggunaan model nilai wajar didukung karena model ini dianggap mendorong transparansi dan pengambilan keputusan yang baik karena model nilai wajar ini mencerminkan kondisi pasar saat itu (Laux & Leuz, 2009).…”
Section: Model Nilai Wajar Dalam Ias 41unclassified
“…The rate of profit earned by farmers every year shifts considerably in relation to the rate of cost in agriculture activity. This study recommends common accounting principles practices that will exercise bookkeeping and managerial accounting that can enhance farmstead administration and generate beneficial farmstead practices (Argiles & Slof, 2000). The existing instrument is similar to the Proposed International Accounting Standard on Agriculture (PIASA) that acts as principal to the advancements of accounting in European agriculture.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%